2018
DOI: 10.1080/03639045.2018.1496449
|View full text |Cite
|
Sign up to set email alerts
|

Propolis emulgel: a natural remedy for burn and wound

Abstract: The formulation F7 with 5% isopropyl palmitate, 5% emulsifier mixture, 1% hydroxyl propyl methyl cellulose, 1% oleic acid, and 10% propylene glycol is a promising formula for better management of wound and burn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
2
15
0
3
Order By: Relevance
“…Gel forming agents in hydrogels exhibit multiple functions such as thickeners (increase the viscosity of formulation) and as emulsifiers (decrease the interfacial tension) to enhance the stability of emulgels (Bonacucina et al., 2009; Javed et al., 2018; Sohail et al., 2018). Thus, emulgels have been researched for the delivery of hydrophobic drug such as propolis, cyclosporine A, and amphotericin B (Shen et al., 2015; Balata et al., 2018; Pinheiro et al., 2019). From various experimental finding regarding emulgel delivery system, it was found that nanosized (generally range from 20 to 500 nm) emulsion gained the advantages of large surface area which allows rapid penetration through the pores to reach the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Gel forming agents in hydrogels exhibit multiple functions such as thickeners (increase the viscosity of formulation) and as emulsifiers (decrease the interfacial tension) to enhance the stability of emulgels (Bonacucina et al., 2009; Javed et al., 2018; Sohail et al., 2018). Thus, emulgels have been researched for the delivery of hydrophobic drug such as propolis, cyclosporine A, and amphotericin B (Shen et al., 2015; Balata et al., 2018; Pinheiro et al., 2019). From various experimental finding regarding emulgel delivery system, it was found that nanosized (generally range from 20 to 500 nm) emulsion gained the advantages of large surface area which allows rapid penetration through the pores to reach the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Pois, segundo a literatura, além de possuir propriedades antioxidantes e moduladoras do sistema imune, exerce função antimicrobiana natural (Park et al, 1998;Santos et al, 2007;Oryan et al, 2018), com poucos efeitos colaterais locais (Lacerda et al, 2011), o que não acontece com a maioria dos antimicrobianos disponíveis no mercado (Ensina et al, 2009;Mota et al, 2010). Ademais, apresenta baixo custo, tornando-se acessível à população (Sforcin et al, 2000;Peruchi et al, 2001;Balata et al, 2018).…”
Section: Resultsunclassified
“…Dentre tantas substâncias naturais estudadas, a própolis verde tem sido apontada como alternativa ao tratamento de inúmeras enfermidades, tanto na medicina humana como na veterinária, sendo amplamente estudadas suas funções (Banskota et al, 2000;Sforcin et al, 2000;Castaldo e Capasso, 2002;Menezes, 2005;Lacerda et al, 2011;Martinotti et al, 2019). Dentre as várias pesquisas utilizando a própolis, algumas revelaram sua eficácia nos processos de cicatrização (Peruchi et al, 2001;Santos et al, 2007;Barbosa et al, 2009;Daneze et al, 2016a,b;Fachini et al, 2016;Balata et al, 2018;Oryan et al, 2018). Contudo, são poucos os estudos que utilizaram a própolis como medicamento no tratamento de feridas cutâneas em cães.…”
Section: Introductionunclassified
“…Biocompatible bioAgNP-propolis-coated sutures had potent antibacterial activity against E. coli and S. aureus and were able to simulate the proliferation of fibroblast [ 83 ]. Furthermore, propolis was used as an active ingredient in emulgel formulation developed for better management of wound and burn healing process [ 84 ]. Recently developed formulations for wound treatment based on bee products are summarized in Table 1 .…”
Section: Health Benefits Of Bee Products With Focus On Regenerative Medicinementioning
confidence: 99%
“…Recently developed formulations for wound treatment based on bee products are summarized in Table 1 . Most of them are prepared with propolis or honey to enhance the wound healing effect [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. Prior to clinical evaluation of these wound-healing formulations, acceptability and efficacy must be assessed in comparison with conventional treatment options.…”
Section: Health Benefits Of Bee Products With Focus On Regenerative Medicinementioning
confidence: 99%